Screening and Referral for Postpartum Depression among Low-Income Women: A Qualitative Perspective from Community Health Workers. (28th April 2011) - Boyd, Rhonda C.; Mogul, Marjie; Newman, Deena; Coyne, James C.
Abstract : Postpartum depression is a serious and common psychiatric illness. Mothers living in poverty are more likely to be depressed and have greater barriers to accessing treatment than the general population. Mental health utilization is particularly limited for women with postpartum depression and low-income, minority women. As part of an academic-community partnership, focus groups were utilized to examine staff practices, barriers, and facilitators in mental health referrals for women with depression within a community nonprofit agency serving low-income pregnant and postpartum women. The focus groups were analyzed through content analyses and NVIVO-8. Three focus groups with 16 community health workers were conducted. Six themes were identified: (1) screening and referral, (2) facilitators to referral, (3) barriers to referral, (4) culture and language, (5) life events, and (6) support. The study identified several barriers and facilitators for referring postpartum women with depression to mental health services.